A protocol for organoids from the gynecomastia patients - Fangjian Shang; Zihao Li; Ji Feng; Qi Wang; Mengyang An; Zengren Zhao; Bo Liu (Frontiers in Bioengineering and Biotechnology)
BackgroundGynecomastia, characterized by benign proliferation of male breast glandular tissue, is a prevalent condition with complex etiologies. However, the absence of effective in vitro models has hindered mechanistic investigations and therapeutic development.MethodsIn this study, we established and characterized organoids derived from the breast tissues of six male gynecomastia patients, including physiological, idiopathic, and hormone-related subtypes. Organoid fidelity was evaluated using hematoxylin and eosin (H&E) staining, immunohistochemistry (IHC), immunofluorescence (IF), and quantitative PCR (qPCR), targeting a panel of lineage-specific and proliferative markers.ResultsThe organoids recapitulated key histological and molecular features of their corresponding source tissues, including epithelial architecture and expression of CK14, CK18, Ki67, and ERα. Marker expression was generally consistent between organoids and tissues at both the protein and transcriptional levels. Notably, ERα protein levels were reduced in organoids, while ESR1 mRNA expression remained stable, suggesting post-transcriptional regulation related to culture conditions.ConclusionOur study presents a practical and reproducible protocol for generating gynecomastia-derived organoids and highlights their utility as a disease-relevant platform for future research in male breast pathology and hormone-related mechanisms.